Nitrogen concentrations in a mangrove creek with a large tidal range, Peninsular Malaysia - Thong, K.L.; Sasekumar, A.; Marshall, N. (Kluwer Academic Publishers, 1993)
We report on various species of nitrogen in subsurface water samples taken at the mouth of Sungai Sementa Besar, a creek about 4.5 km long off the Straits of Malacca and draining a mangrove forest on the west coast of Peninsular Malaysia. This tide-dominated watercourse shows a range greater than 4.5 metres from low to high water during springs, only 1.0 m during neaps, and salinities at the mouth of 30‰ or greater. After heavy rains or when the tides inundate the forest floor, inorganic nitrogen values increase as much as tenfold at the mouth. Particulate and total organic nitrogen also increase at the mouth under these conditions. There were also comparative highs of organic inputs at other times.